2020
DOI: 10.1080/00016357.2020.1786600
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphism rs4284505 in microRNA17 and risk of dental fluorosis

Abstract: Objectives: The aim of this study is to evaluate the association between the single nucleotide polymorphism (SNP) rs4284505 within the gene that codifies microRNA17 (miRNA17) and dental fluorosis (DF) in a group of children. Methods: Children living in a city with fluoridation of public water supplies were included. DF was assessed in erupted permanent teeth by Dean's modified index. The miR-SNP rs4284505 was selected in miRNA17 and genotyping was carried out by real-time PCR. Genotype and allelic distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…These teams analyzed TUFT1 rs4970957 and miRNA17 rs4284505, indicating that alleles A and G increased the risk of dental fluorosis. In addition, a second team reported that the association occurred with the moderate phenotype of the disease [ 24 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These teams analyzed TUFT1 rs4970957 and miRNA17 rs4284505, indicating that alleles A and G increased the risk of dental fluorosis. In addition, a second team reported that the association occurred with the moderate phenotype of the disease [ 24 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…D4: Bias in measurement of the outcome. D5: Bias in the selection of the report result [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Figurementioning
confidence: 99%
“…and is associated with increased dental caries ( 54 , 55 ). Dental fluorosis presents with differing severity in individuals exposed to similar levels of fluoride intake, suggesting the influence of genetic factors and gene-environment interactions ( 56 ).…”
Section: Dental Cariesmentioning
confidence: 99%
“…[18,19] Several studies have reported that genetic polymorphisms can modify the harmful effects of fluoride, such as dental and skeletal fluorosis. [20,21] Studies have also shown that gene polymorphisms may modulate sensitivity to the effects of fluoride exposure on intelligence. For example, polymorphisms of the catechole-o-methyltransferase gene and dopamine receptor-2 gene have been reported to modify the adverse effects of fluoride on IQ scores.…”
Section: Introductionmentioning
confidence: 99%
“…Individual susceptibility (eg, gene polymorphisms) is an important factor that affects the sensitivity of body health to environmental factors [18,19] . Several studies have reported that genetic polymorphisms can modify the harmful effects of fluoride, such as dental and skeletal fluorosis [20,21] . Studies have also shown that gene polymorphisms may modulate sensitivity to the effects of fluoride exposure on intelligence.…”
Section: Introductionmentioning
confidence: 99%